The imagistic web of San myth, art and landscape - Lewis-Williams, J. D. (Southern African Humanities, 2010)
Nineteenth-century texts provided by San people point to parallels and interrelationships between certain myths, paintings and landscapes. Both the myths and the paintings discussed in this article come from the Drakensberg, a dramatic landscape about which the San entertained cosmological beliefs. Transition, a fundamental of San religious thought and art, was embedded in components of the landscape.